2020
DOI: 10.1371/journal.pone.0239982
|View full text |Cite
|
Sign up to set email alerts
|

In vitro singlet state and zero-quantum encoded magnetic resonance spectroscopy: Illustration with N-acetyl-aspartate

Abstract: Magnetic resonance spectroscopy (MRS) allows the analysis of biochemical processes non-invasively and in vivo. Still, its application in clinical diagnostics is rare. Routine MRS is limited to spatial, chemical and temporal resolutions of cubic centimetres, mM and minutes. In fact, the signal of many metabolites is strong enough for detection, but the resonances significantly overlap, exacerbating identification and quantification. Besides, the signals of water and lipids are much stronger and dominate the ent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…39 The quest for a biocompatible molecular marker that supports hyperpolarized long-lived spin order to be used for in vivo imaging applications is still open and has the potential to bring about important new possibilities in MRI. 40 At the core of all these developments is the measurement of the singlet order decay constant (T S ) and its theoretical modelling. 41 The intelligent design of molecules bearing singlet states has led to molecules displaying singlet order lifetimes of the order of hours.…”
Section: Introductionmentioning
confidence: 99%
“…39 The quest for a biocompatible molecular marker that supports hyperpolarized long-lived spin order to be used for in vivo imaging applications is still open and has the potential to bring about important new possibilities in MRI. 40 At the core of all these developments is the measurement of the singlet order decay constant (T S ) and its theoretical modelling. 41 The intelligent design of molecules bearing singlet states has led to molecules displaying singlet order lifetimes of the order of hours.…”
Section: Introductionmentioning
confidence: 99%
“…The longitudinal magnetization (the black line) is transferred to the spin order (I 1z + 2I 2x I 3x + 2I 2y I 3y ) with the highest efficiency. Comparing with the reported singlet-filtered methods for signal selection, including gM2S 43 , SUCCESS 36 , SISTEM 35 , the main advantage of the OC pulses lies on the accurate control of the spin dynamics of a multiple spin system, resulting in the high preparation efficiency of the singlet order of the multiple spin system (see Fig. S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a nuclear singlet spin state/order [28][29][30][31] has been used to select magnetic resonance signals from a specific group and/or molecule in vitro [32][33][34][35] . For example, DeVience et al 36 demonstrated a method known as 'Suppression of Undesired Chemicals using Contrast-Enhancing Singlet States (SUCCESS) to create, preserve and measure the target singlet state produces strong contrast relative to undesired spectral components when the spectra of two molecules nearly overlap.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tayler and Levitt incorporated 18 O isotopic labelling to engender a small 13 C chemical shift difference in a symmetric oxalate molecule [22]; (iii) Altering pH. Pravdivtsev et al adjusted the pH of their solution to tailor the chemical shift difference between the CH 2 group protons of N-acetyl-L-aspartic acid [23]; and (iv) Chemical reactions. Zhang et al forged a symmetrybreaking 1 H chemical shift difference and unlocked access to the LLS of dimethyl maleate by the addition of thiols [24].…”
Section: Introductionmentioning
confidence: 99%